Art of LEGO Design : Creative Ways to Build Amazing Models. - Schwartz, Jordan (No Starch Press, 2014)
The most impressive LEGO models often take careful planning (and lots of pieces), but with some inspiration, a little imagination, and a number of tried-and-true techniques, you too can turn bricks into a masterpiece. In The Art of LEGO® Design, author J.